The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.21091/mppa.2022.4036
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Professional Circus Students’ Psychological Characteristics at Four Strategic Timepoints over the Scholastic Year: A Longitudinal Study Using the Stress Process Model

Abstract: OBJECTIVE: The circus professionalization process entails extensive training to mitigate the high-risk demands which increase stress in artists. In high-risk professions, everyday hassles (challenges) contribute greatly to overall stress. To capture the impact of daily challenges on student-artists, the aim of the current study was to describe the magnitude and pattern of daily challenges as well as their relationships with perceived coping, anxiety, fatigue, and psychological distress. METHODS: Ninety-two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…This could explain a great heterogenity in the body composition of the students in accordance to their backgrounds (Africans, Europeans, South American and Natives) as well as differences in body demands from each circus discipline. A similar diversity in population was noticed by Decker (2020) in Canada. This suggests that biological diversity should be an aspect to be taken into account when a multinational circus school's students is analyzed.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This could explain a great heterogenity in the body composition of the students in accordance to their backgrounds (Africans, Europeans, South American and Natives) as well as differences in body demands from each circus discipline. A similar diversity in population was noticed by Decker (2020) in Canada. This suggests that biological diversity should be an aspect to be taken into account when a multinational circus school's students is analyzed.…”
Section: Discussionsupporting
confidence: 80%
“…So far, the only comparison we can make with professional circus students is with the recent study developed by Decker (2020), who used a more accurate method (DEXA) for body composition assessment of Montreal National Circus School students and finding a very similar result to ours. Concerning BF%, his results showed 16.2% for woman, 8.9% for men and 11.5% for all; while our study was found 16.8% for woman, 7.1% for men and 11.4% for all.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations